Socio-demographic, economic and behavioral determinants of loss to follow-up status among human immunodeficiency virus-infected patients in southern Benin in 2020 - Sossa-Jerome, Charles; Salami, Lamidhi; Adjaffon, Rebecca; Paraiso, Moussiliou N. (International Journal Of Community Medicine And Public Health, 2023)
Background: The recurrence of cases lost to follow-up constitutes a major concern for human immunodeficiency virus (HIV) care programs, particularly in Africa. The present study was carried out to determine the economic and socio-behavioral factors associated with the status of loss to follow-up among HIV-infected patients followed at the Suru Lere Zonal Teaching Hospital Center in Benin. Methods: This was a case-control study carried out with 41 cases selected for convenience and 82 controls retained according to a reasoned choice. Matching was done on the variables age (±5 years), sex and year of initiation of treatment. The data collected using questionnaires and counting sheets then entered using the Epi data 3.1 software were analyzed using the STATA 11 software. A multiple conditional logistic regression model at the 5% threshold was used to determine factors associated with “lost to follow-up” status. Results: In the sample, the average age of the people surveyed was 41±9 years for both cases and controls and women were predominantly represented (63.41%). The factors associated with the status of loss to follow-up were the non-existence of a means of transport (p=0.008), the lack of nutritional support (p=0.01), incorrect knowledge about antiretroviral treatment such as “ARVs cure HIV/AIDS” (p=0.002) or “treatment can be stopped when you feel better” (p=0.014). Conclusions: This study revealed the significant association of “lost to follow-up” status with socio-demographic, economic and behavioral factors among people on ARV treatment. These results will lead to better guide the care of these patients and improve the performance of the AIDS control program.